2013
DOI: 10.1115/1.4025269
|View full text |Cite
|
Sign up to set email alerts
|

Free Convection in Antisymmetrically Heated Vertical Channels

Abstract: Free convection in a vertical channel with antisymmetrical heating is a special case that has not received a great deal of attention in the literature. Antisymmetrical heating is where the hot wall is heated above the ambient temperature by the same amount that the cold wall is cooled below the ambient, giving equal but opposing buoyancy forces inside the channel. An experimental model was constructed to study antisymmetrical heating inside an isothermally heated vertical channel. Flow visualization was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…With respect to the temperature and the vertical velocity component (see Figure 5), the research found maximum differences of about 1% and 4.5%, respectively. We can conclude that even though the numerical model was considered in laminar steady-state flow and thermal radiation has been neglected, all cases have a good agreement regarding experimental data 37 and the analytical solution for mixed convection in a vertical channel. 38…”
Section: Numerical Methods and Verificationmentioning
confidence: 66%
See 2 more Smart Citations
“…With respect to the temperature and the vertical velocity component (see Figure 5), the research found maximum differences of about 1% and 4.5%, respectively. We can conclude that even though the numerical model was considered in laminar steady-state flow and thermal radiation has been neglected, all cases have a good agreement regarding experimental data 37 and the analytical solution for mixed convection in a vertical channel. 38…”
Section: Numerical Methods and Verificationmentioning
confidence: 66%
“…The numerical code was validated with the experimental solution for natural convection in an antisymetrically heated vertical channel reported by Roeleveld et al. 37 Table 3 shows the comparison of the average Nusselt number at the hot wall between the present numerical solution and experimental results for three different Rayleigh numbers ( Ra = 1.48 × 10 + 3, Ra = 4.79 × 10 + 3, and Ra = 1.18 × 10 + 3). As can be observed, the results showed maximum deviations between 6.1 and 7.5% for all Ra numbers under analysis.…”
Section: Numerical Methods and Verificationmentioning
confidence: 99%
See 1 more Smart Citation